Antiosteoporosis and bone protective effect of dieckol against glucocorticoid-induced osteoporosis in rats - Wang, Hao; Yang, Leigang; Chao, Junwei (Frontiers in Endocrinology, 2022)
Glucocorticoids (GC) induces the secondary osteoporosis, which resultant fractures cause the significant morbidity. In this study, we scrutinized the antiosteoporosis effect of dieckol against glucocorticoid-induced osteoporosis in rats. Sprague-Dawley (SD) rats were selected for the current study and dexamethasone (2.5 mg/kg) was induce the osteoporosis and the rats were received the dieckol (test) and alendronate (standard) for 20 weeks. Bone turnover, microCT, antioxidant, inflammatory cytokines, nutrient and hormones parameters. Dieckol significantly (P<0.001) suppressed the body weight and boosted the uterine and vagina weight. Dieckol significantly enhanced the level of Tb.N and suppressed the BV/TV, Tb.Sp, BS/BV, Tb.Th. Dieckol significantly (P<0.001) increased the level of OC and reduced the level of BGP, ACP, ALP and β-CTx. Dieckol significantly boosted the level of MDA and suppressed the level of GSH, CAT and SOD along with suppression of inflammatory cytokines like TNF-α, IL-1β and IL-6. Dieckol remarkably suppressed the level of calcium, potassium, magnesium and 25(OH)vitamin D. Dieckol significantly (P<0.001) boosted the level of estradiol and suppressed the level of parathyroid hormone and TRAP. Dieckol significantly suppressed the level of RANKL and boosted the level of OPG. Collectively, we can say that dieckol demonstrated the antiosteoporosis effect against glucocorticoid-induced osteoporosis in rats.